Activation of brown adipose tissue in hypothyroidism. (3rd October 2015) - Lapa, Constantin; Maya, Yoshifumi; Wagner, Martin; Arias-Loza, Paula; Werner, Rudolf A.; Herrmann, Ken; Higuchi, Takahiro
Abstract: Background Brown adipose tissue (BAT) attracts growing interest as a potential therapeutic target for obesity and diabetes. Hyperthyroidism is well-known to increase BAT activity, but the role of hypothyroidism is controversial. We aimed to investigate the association between different thyroid hormone (TH) states and BAT activity. Methods FDG-PET studies were retrospectively evaluated in thyroid cancer patients after total thyroidectomy both at euthyroidism during TH replacement or at hypothyroidism after TH cessation. Serum TH levels were compared between patients with active BAT and control patients with non-active BAT matched for age, gender, and body mass index. Additionally, animal experiments with controls ( n  = 5) and hypothyroid rats ( n  = 5) were performed. Results Out of 124 patients, 6 patients with active BAT were identified. These patients showed significantly higher thyroid-stimulating hormone (TSH) levels than matched controls ( P  < 0.05). In animal experiments, all hypothyroid animals showed BAT activation at room temperature (24 °C), whereas controls did not ( P  < 0.001). Increased BAT activity was also confirmed by increased expression of UCP-1 and D2. Conclusions Increased BAT metabolism appears to be related with hypothyroidism, which might be the result of a feedback mechanism to maintain body temperature in a state of reduced basal thermogenesis. Future research needs to explore the underlying mechanistic and biological implications. Key Messages: Increased brown adipose tissue (BAT) metabolism appears to be related with hypothyroidism, which might be the result of a feedback mechanism to maintain body core temperature in a state of reduced basal thermogenesis.